In vivo immunohistochemical investigation of the effect of the topical application of growth hormone on the osseointegration of cpTi implant - Abdul Naser H Warwar; Ban A Ghani (College of Dentistry/ University of Baghdad, 2014)
Background: Dental implants are a suitable option for the replacement of some or all missing teeth. The successful insertion of a biocompatible material into living tissue with little to no evidence of rejection has revolutionized medicine and dentistry. An increase in bone response was observed with local administration of growth hormone around dental implants. Growth hormone may act as a bone stimulant in the placement of endosseous dental implants and enhances osseointegration. The aim of the study was to evaluate immunohistochemically the effect of the topical application of growth hormone on the osseointegration of cpTi implant. Materials and Methods: Eighty titanium screw implants were inserted in the tibia of the forty adult rabbits. Growth hormone was applied on experimental implants. Immunohistochemical tests were performed on the implants of both control and experimental groups for (3 days1, 2, and 6 weeks) healing intervals. Results: Titanium implants coated with growth hormone revealed an early bone formation, minerlization and maturation in comparison to control. Immunohistochemical findings revealed positive expression for VEGF in experimental implant in comparison to control one. Conclusion: Topical application of growth hormone may act as a bone stimulant in the placement of endosseous dental implants and enhances osseointegration.